Efektivitas Metode Index Card Match dalam Meningkatkan Penguasaan Kosakata Bahasa Arab Siswa Kelas IV Sekolah Qur’an Ibnu Katsir - Hidayat, Fajar; Sya'bani, Muhammad Zaky; Kasmudi (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2024)
The aim of this research is to determine the level of success and effectiveness of using the Index Card Match learning method in mastering Arabic vocabulary for class IV students at the Ibnu Katsir Qur'an School in Bandar Lampung. The questions in this research include "What is the effectiveness and level of success of using the Index Card Match learning method on the Arabic vocabulary mastery of class IV students at the Ibnu Katsir Qur'an School in Bandar Lampung?" This research is quantitative research. The subjects in this research were all 31 class IV students at the Ibnu Katsir Qur'an School in Bandar Lampung, consisting of two classes. Based on research that has been carried out, the results of descriptive statistical analysis show that the average value of learning outcomes for experimental class students through the posttest is 82.50, which is better when compared to the average value of learning outcomes for students who do not apply the Index Card Match method via the posttest. only 60.00. This shows that there are differences in the level of ability of students using the Index Card Match method and those using conventional methods.